MARTINS FILHO, Amilcar V.; CABRAL, Cleber Araújo (Org.). "1929 Leite Criôlo Bello Horizonte": edição fac-símile. Belo Horizonte: Instituto Cultural Amilcar Martins, 2012. 152 p. - Tolentino, Thiago (Em Tese, 2013)
Resenha.